DAYA SAING EKSPOR LADA INDONESIA KE VIETNAM, AMERIKA SERIKAT DAN INDIA - Karo-Karo Sitepu, Rasidin; Grace Tambunan, Greyuni; Yohanna Natalina Damanik, Desri; Erlikasna Br Tarigan, Elfira; Fadhilla Salsabila, Raden; Daniyal Stis, Muhammad (Sekolah Tinggi Ilmu Ekonomi GICI, 2024)
Pepper is a spice commodity that has the potential to be developed due to its superior quality. This study aims to analyze the competitiveness of pepper to identify promising export markets and potential development in destination countries. The data used is secondary data which is a combination of time series data and cross section data. The range of years used starts from 2017 to 2022 sourced from the Central Statistics Agency (BPS), Trade Map, and Uncomtrade. Data analysis is used with the Revealed Comparative Advantage (RCA), Export Product Dynamics (EPD), and Export Competitiveness Index (ECI) methods. The results of the analysis show that Indonesian pepper exports to destination countries such as Vietnam, USA, and India have a competitive advantage and comparative advantage in the destination country because the RCA value is more than 1. The competitiveness of Indonesian pepper exports to destination countries varies, the average ECI value shows that Indonesia has good competitiveness in pepper exports to India, but tends to be weaker than Vietnam and the United States. ECI values > 1 indicate that Indonesia has a competitive advantage in the pepper export market to India, while ECI values < 1 for Vietnam and USA indicate that Indonesia has lower competitiveness in these export markets.